Penilaian psikometrik bagi Sleep Habit Inventory (SHI) versi bahasa Melayu dalam kalangan kanak-kanak di Malaysia - Suwaibah Zakaria,; Suzana Mohd Hoesni,; Roseliza Murni Ab Rahman,; Zainah Ahmad Zamani, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Sleep is a vital necessity need for children. The process of child development will be affected if they did not get enough sleep. Children sleeping needs can be met if they are given a sleeping routine to suit their age. As children are individuals who still depends entirely on their parents or guardians, their routine sleeping arrangements will be directly influenced by how their parents or guardians manage their sleep schedule. The purpose of the study was to assess psychometric aspect of Sleep Habit Inventory (SHI) Malay version. This instrument was used to measure sleep habit of young children. The instrument divided to three components that measure sleep routine, rhythm and separation affects. Overall scale consisted of 17 items. SHI was translated into Malay language by using back to back translation procedure proposed by Brislin. Respondents of the study were 150 working mothers with 18 to 36 years old child at Kota Kinabalu, Sabah. The result of exploratory factor analysis (EFA) found that 15 from 17 items were accepted due to factor loading greater than 0.6. and all components extracted achieved the value of alpha cronbach minimum 0.7. As conclusion, this instrument can be used to measure child sleep habit in local context especially in Sabah.